Studies in Managerial Process and Organizational Behavior - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1973)
This article reviews "Studies in Managerial Process and Organizational Behavior" by John H. Turner, Allan C. Filley and Robert J. House.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z